Hot machining of difficult-to-cut materials: A review. (2021) - Pandey, Kshitij; Datta, Saurav
Abstract: Hot machining is a thermally-assisted metal cutting process which is favourably exercised when machining of difficult-to-cut materials. In general, difficult-to-cut materials are characterized by their high-temperature strength (hot strength), low thermal conductivity, and dominant work-hardening tendency. Hence, machining of difficult-to-cut materials is associated with high cutting force, high specific power consumption, detrimental tool wear, and degraded machined surface integrity. Machining efficiency may be improved by adapting the principle of hot machining which utilizes an external heat source to preheat the workpiece. Preheated workpiece undergoes adequate thermal-softening which causes easy material removal by application of lower cutting force. In addition, tool life, and machined surface finish are significantly improved when compared to conventional machining. The present reporting focuses on state-of-art in the area of hot machining applied to difficult-to-cut materials. Types of hot machining in perspective of different heat sources utilized and associated merits/ demerits are thoroughly discussed. Future research avenues on this particular topic are highlighted as well.